Cirrhosis and diabetes mellitus - Niebisz, Agnieszka (Przewodnik Lekarza/Guide for GPs, 2005)
Diabetes is diagnosed in over 15% patients with liver cirrhosis, in the higher percent of diabetes was confirmed in persons in alcoholic and post inflammatory liver cirrhosis. The pathogenesis of carbohydrates metabolism disorders is still unknown, but in majority of this patients insulin resistance secondary to hiperinsulinemia is diagnosed. Not without meaning is progress liver insufficiency, formation of collateral circulation and the higher concentration of antagonist to insulin hormones. Often after alcohol abuse the pancreas is also damaged, and this patients needs at the beginning of treatment higher doses of insulin. The best method of carbohydrates metabolism disorders treatment in patient with liver cirrhosis is intensive insulinotherapy according to glycemia and to present clinical state. Very important is explanation to patients the essence of these chronic diseases to determine applicable therapy aspect.